Enhanced Spatial Planning as a Precondition for Sustainable Urban Development - Ionescu-Heroiu, Marcel; Neagu, Marina; Taralunga, Nicolae; Ortiz, Pedro; Petrovici, Norbert; Moldovan, Ciprian; Panescu, Eugen (World Bank, Washington, DC, 2014)
This report provides an analysis of the spatial planning system in Romania and suggests ways in which it can be improved. Romania has recently experienced a proliferation of plans, strategies, and policies developed at all administrative levels. Adding to this, the analysis of territorial and urban development in Romania reveals important dynamics and challenges, such as uncontrolled expansion of built perimeters, increased pressures on transport infrastructure and utilities, and aggressive urban interventions causing disruptions and redundancies in the urban fabric. Such dynamics require new system architecture, including the design and implementation of new instruments, enhancing and mainstreaming existing ones, as well as building capacity. This report provides recommendations for: 1) the correlation and harmonization of different types of plans; 2) the simplification of the framework of planning in Romania; and 3) the development of a planning system that will better integrate national and European Union (EU)-funded initiatives.